2016
DOI: 10.1177/0954409716657849
|View full text |Cite
|
Sign up to set email alerts
|

Track geometry degradation and maintenance modelling: A review

Abstract: Increased demand for railway transportation is creating a need for higher train speeds and axle loads. These, in turn, increase the likelihood of track degradation and failures. Modelling the degradation behaviour of track geometry and development of applicable and effective maintenance strategies has become a challenging concern for railway infrastructure managers. During the last three decades, a number of track geometry degradation and maintenance modelling approaches have been developed to predict and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 85 publications
(204 reference statements)
0
100
0
1
Order By: Relevance
“…They indicated that there is a significant difference between the results predicted by different previously-developed empirical models. Soleimanmeigouni et al [11] reviewed and classified available models for track geometry degradation. Empirical models may help engineers to make a rough maintenance forecast of railway tracks; however, these models do not have a theoretical basis nor provide any fundamental insight.…”
Section: Imentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that there is a significant difference between the results predicted by different previously-developed empirical models. Soleimanmeigouni et al [11] reviewed and classified available models for track geometry degradation. Empirical models may help engineers to make a rough maintenance forecast of railway tracks; however, these models do not have a theoretical basis nor provide any fundamental insight.…”
Section: Imentioning
confidence: 99%
“…12and (13) satisfy the periodicity conditions introduced in Eqs. 10and (11). One can now take the Fourier transform of the both sides of Eqs.…”
Section: A Frequency-domain Model For Wheel/track Dynamicsmentioning
confidence: 99%
“…Due to its operation, railroads that are used as roads for trains will experience quality degradation in some of their components [5] [6] including in railroad structures such as fractures in rail weld joints, damage to rail fasteners, wear on rails and cracks in concrete bearings. The dominant incidence of train accidents in Indonesia is the collapse of the carriages caused by the spread of cracks in rail fractures, cracks in concrete pads, loose fastening of rails, failure of railroad structures, land subsidence, and human error.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that, in railway infrastructure, the rate of degradation is not quick. However, this process can lead to system failure with great human casualties and significant financial loss if necessary maintenance actions are not considered [6,7]. To keep the tram services reliable and comfortable, implementing efficient maintenance strategies is necessary [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tram stops are mostly not grade-separated and most of modern vehicles are low-floor. Consequently, boarding and alighting is easier and faster for passenger with disabilities and older people [5,6].…”
Section: Introductionmentioning
confidence: 99%